Regnum Et Ecclesia - Buckler, Francis W. (Church history, 1934)
The nineteenth and twentieth centuries have witnessed a renaissance of Oriental studies and interest, only to be compared with the classical Renaissance of the fifteenth and sixteenth centuries. For the Church historian, the two movements must be regarded as counterparts, for while the Renaissance drove men back to the Greek Testament, the oriental renaissance has penetrated to the region behind it. It has, moreover, opened up the whole of the region, which was but dimly reflected and ill-understood by Graeco-Roman writers, between the limits of the oikoumenē of Alexander the Great and those of the Roman Empire.